Pembentukan hidrogen dari koh menggunakan katalis aluminium foil dari limbah bungkus rokok - Deska Eka Safitry; Hernowo Widodo (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: As we know, at this time the State of Indonesia is experiencing an energy crisis due to the increasing number of population which has a direct effect on fuel consumption. Hydrogen is very likely to be an alternative fuel for the future. Findings: The hydrogen production process can be carried out biologically or chemically. Chemical production of hydrogen is to use alkaline aluminum to be used as an alkaline aluminum fuel cell. An alkaline-air aluminum fuel cell is a series of aluminum anodes in an alkaline solution and oxygen gas in the cathode that will produce electrical energy. Methods: This research tries to utilize aluminum foil waste (Cigarette Wrapper) as a source of aluminum for hydrogen production. For this reason, research into the production of hydrogen gas from aluminum foil waste using a KOH catalyst. Hydrogenation is done by the process of Hydrognation with temperatures of 25 ° C, 30 ° C, and 40 ° C, with the activator used is Potassium Hydroxide with concentrations of 1M, 2M, 3M, and 4M. Conclusion: The results showed that at 25 ° C with a concentration of 1M there was a volume weight of 286.04 ml. The 2M concentration contained a volume weight of 165.31. 3M concentrations have a volume weight of 118.80 ml. The 4M concentration contained a volume weight of 112.90 ml. At a temperature of 30 ° C with a concentration of 1M there is a volume weight of 217.19 ml. The 2M concentration contained a volume weight of 271.22 ml. 3M concentration contained a volume weight of 273.48 ml. 4M concentration was 272.79 ml. At 40 ° C with a concentration of 1M there is a volume weight of 927 ml. The 2M concentration contained a volume weight of 640.9 ml. 3M concentration contained a volume weight of 453.6 ml. and the 4M concentration contained a volume weight of 299.7 ml. The best results are shown in KOH Activator temperature 40 ° C with a volume weight of 299.7 ml and a concentration of 4M.